Effect of Different Derivatization Protocols on the Calculation of Trophic Position Using Amino Acids Compound-Specific Stable Isotopes - Martinez, Stephane; Lalzar, Maya; Shemesh, Eli; Einbinder, Shai; Goodman Tchernov, Beverly; Tchernov, Dan (Frontiers in Marine Science, 2020)
Amino acids compound-specific nitrogen stable isotope (AA-CSIA) is an emerging tool in ecology for understanding trophic system dynamics. While it has been successfully used for several independent studies across a range of environments and study locations, researchers have encountered calculation issues for determining trophic position values. Most studies introduce modifications to the constants of trophic position equation calculations, but then fail to account for the equation variations when comparing the results of separate research studies. The acceptance of this approach is related to the underlying presumption that no addition of the exogenous nitrogen atom occurs in the different methods and, therefore, such variations should not affect the outcome. In this paper, we evaluate the use of the EZfaast amino acid derivatization kit (chloroformate) and compare it to the isotopic results of two other derivatization methods. We highlight new considerations for working with AA-CSIA that might account for some of the variations in the results and lead researchers to modify constants in the equation. This likely requires developing the unique constants per derivatization method in order to be able to compare the trophic position results across different studies.